1990
DOI: 10.1002/jsfa.2740500109
|View full text |Cite
|
Sign up to set email alerts
|

Rates of fermentation and short chain fatty acid and gas production of six starches by human faecal microbiota

Abstract: Six starches (wheat, kidney bean, rice, corn, amylopectin and amylose) were fermented in vitro with mixed human faecal microbiota for 2,4,6,8,12 and 24 h to determine differences in rates of fermentation, and production of short chain fatty acid (SCFA) and gas. The starches difered significantly in rates of fermentation with wheat and rice starches being completely fermented by 12 h whereas all other starches had disappeared by 24 h. However, individual and total SCFA production g-' starch fermented did not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 24 publications
2
13
2
Order By: Relevance
“…This table shows that the composition of end-products formed influences the amount of gas produced. Between gas production and total VFA formation in vitro a close relationship has been reported (O'Hara and Ohki 1973;Naga and Harmeyer 1975;Datta Roy et al 1976;McBurney et al 1990). However, no explanation has been given by these authors for different amounts of gas produced upon fermentation of different carbohydrates.…”
Section: Introductionmentioning
confidence: 89%
“…This table shows that the composition of end-products formed influences the amount of gas produced. Between gas production and total VFA formation in vitro a close relationship has been reported (O'Hara and Ohki 1973;Naga and Harmeyer 1975;Datta Roy et al 1976;McBurney et al 1990). However, no explanation has been given by these authors for different amounts of gas produced upon fermentation of different carbohydrates.…”
Section: Introductionmentioning
confidence: 89%
“…By using human faeces as an inoculum [27], it was shown that six different sources of starch, while having the same total SCFA production, differed in their rates of gas production. They thus showed that the measurements of gas production more likely reflected the fermentation rate in vivo.…”
Section: Measurements Of Whole Microbial Population Activitymentioning
confidence: 99%
“…RS can be classified into three major types (38): starch entrapped in the cell wall of plants and thereby physically inaccessible to aamylase (RS 1); starch stored in granules in the native crystalline form, which can be made accessible to enzymes by gelatinization (RS 2), and finally starch that has retrograded as a result of cooling of gelatinized starch (RS 3). Like NSP, different starches are fermented to various extents (39,40), and in rats retrograded starch has been found to be less fermented than native starch (RS2) (40).…”
Section: Impact Of Substratementioning
confidence: 99%